Uma abordagem geral sobre empreendedorismo e empresas Startups de biotecnologia no Brasil - César, Dayani Franceschini [UNESP] (2021)
Entrepreneurship involves the entire process from identifying an opportunity to putting it into practice as a business. Innovation, in turn, is the instrument through which change is enjoyed as an opportunity. Combining the two concepts, "startups" stand out as young companies with a strong technological base, which bring innovative and revolutionary products. In this context, the present work was based on the study of reports from the Global Entrepreneurship Monitor (GEM) from 2000 to 2019 and mapping of presents startups in the country carried out by Abstartups to establish the panorama in which biotechnology startups are found in Brazil. As a result, high rates of entrepreneurial activity were revealed, which placed the country among the most entrepreneurial nations globally. However, innovation both in relation to the products and services offered and as the technology used in the processes, proved to be rare, with the businesses mostly focused on the services sector, with little investment of resources, regulation and technical knowledge. Thus, actions such as pedagogical projects aimed at entrepreneurship, strengthening technology parks and incubators that support new and growing businesses, and strengthening the interaction between universities and companies, proved necessary for the country to extend its relevance to sectors of strong technological innovation, in which biotechnology startups operate.